The Synergy of Entrepreneurship Education, Family Environment, and Income Expectations: A Key to Shaping Entrepreneurial Attitudes and Intentions Among the Millennial Generation - Suprapto, Suprapto; Herliansyah, Yudhi; Herminingsih, Anik; Kaidah, Sri (Universitas Muhammadiyah Ponorogo, 2025)
The increase in the number of new entrepreneurs has become a crucial strategy in addressing high unemployment rates and accelerating national economic growth. This study aims to analyze the influence of entrepreneurship education, family environment, and income expectations on entrepreneurial intention, while considering the mediating role of entrepreneurial attitude. A quantitative approach was employed using a survey method, involving 412 university students as respondents, with data analyzed through Partial Least Squares (PLS) technique. The results indicate that entrepreneurship education has a direct, positive, and significant effect on shaping students’ entrepreneurial attitudes. Similarly, income expectations significantly contribute to strengthening entrepreneurial attitudes. In contrast, the family environment variable shows no significant relationship with either entrepreneurial attitude or intention. Further findings reveal that entrepreneurial attitude plays a critical mediating role in shaping students’ intentions to start a business. Additionally, both entrepreneurship education and income expectations also exhibit a direct and significant influence on entrepreneurial intention. The novelty of this study lies in mapping the mediating role of entrepreneurial attitude in bridging the relationship between external factors (entrepreneurship education and income expectations) and entrepreneurial intention an area that has not been extensively explored in previous research. The implications of these findings provide a conceptual foundation for higher education institutions in designing more targeted entrepreneurship development strategies.